Merriam-Webster's reader's handbook (Merriam-Webster, 1997)
This reference book, from the combined resources of Merriam-Webster and Encyclopaedia Britannica, includes descriptions for every major genre, style, and era of writing. Nearly 2,000 entries, including Greek and Latin terminology. A must-have for every serious reader.